Triple Bottom Line Study: Sustainability, Technology Utilization, and Social Media Effectiveness in MSMEs: A Case Study of MSMEs in Cirebon Regency - Listanti, Ruri Virginia; Dinny Nurhayati Fadillah; Destiana, Rina (Indonesian Journal of Advanced Research, 2024)
Micro, Small and Medium Enterprises are a business unit that dominates the activities of the current economic sector, so its sustainability needs to be considered. Along with its development, business actors are required to not only pay attention to profits, but also to pay attention to the environment and society. This is in line with the Triple Bottom Line (TBL) concept which has a tendency to measure business sustainability through three approaches, namely economic, environmental and social. This research was conducted to examine whether the Triple Bottom Line concept has been widely carried out by MSME actors, especially those in Cirebon district, by supporting the Triple Bottom line which includes sustainability, technology utilization, and social media effectiveness.